The Criterion of Maximum Profits in the Theory of Investment - Lutz, F A. (Quarterly Journal of Economics, 1945)
Three logical possibilities as to what an entrepreneur should maximize: the internal rate of return, total profits, rate of profit over cost, 56. — I. The use of these criteria in the literature on the theory of capital and interest, 57. — II. The case of tree-growing: the internal rate of return, 63; total profits, 66; choice between them when a market rate of interest exists, 68; when no market rate exists, 70. — III. Total profits vs. rate of profit over cost, 71. — Where entrepreneur's funds are not limited, 75. — Financing by stock and by debts, 76.